(3Tje JTeTs - (3eMeO GdjOGdj Hf GdeNJGQ Hf eMeO SYjO GdOjeGfj,J (B1164 (3g` s
(3ChdgG (B:s
(3gPG PcQ Tje CSdGafG GdJTeTjI hPcQ CeQ JTeT hPcQ HYV CMhGdgG CeG Tje GdRGhjI agi MbjbI GdJeSc HSfI QShd Gddg hGdYaf YdjgG HGdfhGLP abO CSShG SjQJge hCMcehgG HGdTQY s
(3BNQgG (B:s
(3hcGf CSdGafG jMPQhf ef GdfXQ Edi hLhg GdXdeI hGdSdGWjf , hjCeQhf HZV GdCHUGQ Yfge , hjbhdhf (B: (3Ef GdfXQ ai hLhgge jbSi GdbdH GfJgi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI bOjeI JGeIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJGQjNs